Muslim Women's Studies - Mohja Kahf (International Institute of Islamic Thought, 1996)
Politics, Gender, and the Islamic Past: The Legacy of Aisha hint Abi Bakr. By D. A. Spellberg. New York: Columbia University Press, 1994, 243 pp. Qur'an and Woman. By Amina Wadud-Muhsin. Kuala Lumpur: Fajar Bakti, 1992, 118 pp. Denise Spellberg's survey of the legacy of 'A'ishah and Amina Wadud-Muhsin's exegesis of the Qur'anic exposition of gender are forays in the field of Muslim women's studies. Both works study the place of Muslim women in the textual heritage of the community, but their points of departure are different. Spellberg proposes that 'A'ishah's legacy, a product of exclusively male writings in texts from the classical Islamic centuries, is a reflection of Muslim men's interpretations of early Islamic history and their opinions about the proper place of women in their own time. Such interpretations, Spellberg shows, are charged with the political tensions of their contemporary societies. Yet 'A'ishah 's "legacy alone defied idealization as completely as it denied comfortable categorization" by the Muslim men whose texts represent and construct her, Spellberg asserts (p. 190). Wadud-Muhsin acknowledges the way in which another copious Islamic scholarship emerged, motivated by the need to understand the Qur'anic utterances about women. Her focus is not, however, on those interpretive texts of men that form an authoritative tradition explaining the meaning of the Qur'an. Wadud-Muhsin argues that the question of woman in the Qur'an must be reconnected directly to the primary text. She proposes approaching the Qur'anic text without the assumptions about gender of the classical interpreters, whose work constitutes the Islamic tradition of exegesis, but also without the assumptions that undergird contemporary feminist readings of the Qur'an. She offers a herrneneutical method for understanding the place and meaning of gender in the Qur'an, based on the consistencies of the Qur'an itself: its contexts, language, and the worldview of its texts as a whole. The effect of this, Wadud-Muhsin suggests, would be to transcend the gender biases of narrower reading methods and arrive at a fuller appreciation of the text's guidance for men and women. Both works began as dissertations, Spellberg's in history, WadudMuhsin's in religious studies. Each brings to Muslim women's studies a node of questions about the process of textual interpretation. The ...